1999
DOI: 10.1039/a904575i
|View full text |Cite
|
Sign up to set email alerts
|

Structure, conformation, anomeric effects and rotational barriers in the HERON amides, N,N ′-diacyl-N,N ′-dialkoxyhydrazines

Abstract: N,NЈ-Diacyl-N,NЈ-dialkoxyhydrazines are HERON amides that exhibit theoretical and physical properties of bisheteroatom-substituted amides. Amide nitrogens are pyramidal and they adopt a preferential conformation which permits an anomeric interaction in which one nitrogen overlaps strongly with the adjacent N-O σ* orbital. A crystal structure of N,NЈ-di(p-chlorobenzoyl)-N,NЈ-diethoxyhydrazine 4d has been obtained which confirms these properties in the solid state. Infrared data for ten such hydrazines indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 18 publications
5
25
0
Order By: Relevance
“…In anomeric amides both effects disappear on account of the sp 3 hybridization at nitrogen and barriers to isomerization have been found to be drastically reduced or are too low to be measured by dynamic NMR methods (4,10). Ab initio calculations confirm these properties (4,9,10,15).…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…In anomeric amides both effects disappear on account of the sp 3 hybridization at nitrogen and barriers to isomerization have been found to be drastically reduced or are too low to be measured by dynamic NMR methods (4,10). Ab initio calculations confirm these properties (4,9,10,15).…”
Section: Introductionsupporting
confidence: 52%
“…In a recent study we have demonstrated that these hydrazines exhibit all the hallmarks of anomeric amides (15). Their carbonyl stretch frequencies in solution are in the range of 1700-1744 cm -1 , while those of their precursor hydroxamic esters are in the range 1680-1690 cm -1 (4,15).…”
Section: Rearrangement Of the Intermediate N-alkoxy-n-(n-methyl-mentioning
confidence: 99%
See 2 more Smart Citations
“…5 Structurally, these mutagens are members of the class of so-called anomeric amides which have two electronegative atoms bonded to the amide nitrogen. [6][7][8][9] This results in strong pyramidalisation of the amide nitrogen to satisfy the electron demand of the heteroatoms and the nitrogen lone pair is consequently far less conjugated with the amide carbonyl than is the case in primary amides, secondary and tertiary N-alkylamides, or even hydroxamic esters which have only one oxy-substituent. Such amides have high carbonyl stretch frequencies (1720-1740cm -1 ) and low amide isomerisation barriers (Figure 1(a)) and, in addition, they can support an anomeric effect at the amide nitrogen.…”
Section: Introductionmentioning
confidence: 99%